Nicotinic acetylcholine receptors in attention circuitry: the role of layer VI neurons of prefrontal cortex - Proulx, Eliane (Springer Basel, 2013)
Cholinergic modulation of prefrontal cortex is essential for attention. In essence, it focuses the mind on relevant, transient stimuli in support of goal-directed behavior. The excitation of prefrontal layer VI neurons through nicotinic acetylcholine receptors optimizes local and top-down control of attention. Layer VI of prefrontal cortex is the origin of a dense feedback projection to the thalamus and is one of only a handful of brain regions that express the α5 nicotinic receptor subunit, encoded by the gene chrna5. This accessory nicotinic receptor subunit alters the properties of high-affinity nicotinic receptors in layer VI pyramidal neurons in both development and adulthood. Studies investigating the consequences of genetic deletion of α5, as well as other disruptions to nicotinic receptors, find attention deficits together with altered cholinergic excitation of layer VI neurons and aberrant neuronal morphology. Nicotinic receptors in prefrontal layer VI neurons play an essential role in focusing attention under challenging circumstances. In this regard, they do not act in isolation, but rather in concert with cholinergic receptors in other parts of prefrontal circuitry. This review urges an intensification of focus on the cellular mechanisms and plasticity of prefrontal attention circuitry. Disruptions in attention are one of the greatest contributing factors to disease burden in psychiatric and neurological disorders, and enhancing attention may require different approaches in the normal and disordered prefrontal cortex.